2014
DOI: 10.1126/science.1253836
|View full text |Cite
|
Sign up to set email alerts
|

Advances in skin grafting and treatment of cutaneous wounds

Abstract: The ability of the skin to repair itself after injury is vital to human survival and is disrupted in a spectrum of disorders. The process of cutaneous wound healing is complex, requiring a coordinated response by immune cells, hematopoietic cells, and resident cells of the skin. We review the classic paradigms of wound healing and evaluate how recent discoveries have enriched our understanding of this process. We evaluate current and experimental approaches to treating cutaneous wounds, with an emphasis on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
516
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 716 publications
(527 citation statements)
references
References 55 publications
1
516
0
10
Order By: Relevance
“…CXCL-8 may also promote homing of vascular endothelial cells to the skin ulcer area to increase angiogenesis, reduce hypoxia and accelerate ulcer healing. The healing of skin wounds involves the secretion of numerous cytokines and interactions between fibroblasts, vascular endothelial cells and various other cell types (39). As the present study evaluated the effect of CXCL-8 on only vascular endothelial cells, studies into the effects of CXCL-8 on other cell types are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCL-8 may also promote homing of vascular endothelial cells to the skin ulcer area to increase angiogenesis, reduce hypoxia and accelerate ulcer healing. The healing of skin wounds involves the secretion of numerous cytokines and interactions between fibroblasts, vascular endothelial cells and various other cell types (39). As the present study evaluated the effect of CXCL-8 on only vascular endothelial cells, studies into the effects of CXCL-8 on other cell types are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that hypoxia stimulates HeLa cells to express high levels of CXCL-8, which subsequently promotes vascular endothelial cell homing and accelerates angiogenesis, leading to a reverse in the hypoxic environment of the tumor tissue, increased tumor cell proliferation and inhibition of cell apoptosis (38). During the process of skin wound healing, macrophages secrete high levels of CXCL-8, which then stimulates the recruitment of fibroblasts, vascular endothelial cells, hair follicle stem cells and others to the skin defect area through binding to CXCR1/2 (39)(40)(41). CXCL-8 also promotes vascular endothelial cell adhesion, accelerates angiogenesis, increases the deposition of extracellular matrix and promotes wound healing, which further indicates the importance of CXCL-8 in wound healing (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of recent years have shown that usage of iPSCs makes it possible to obtain effective tissue-engineered products for regenerative medicine including treatment skin wounds [39]. A good illustration is the work of Itoch et al [40] in which they elaborated a protocol of IPSCs differentiation into keratinocytes and dermal fibroblasts to be used in the treatment of recessive dystrophic epidermolysis bullosa.…”
Section: A Cellular Componentmentioning
confidence: 99%
“…[2][3][4] Numerous growth factors, such as epidermal growth factor (EGF), transforming growth factor beta (TGF-β), fibroblast growth factor (FGF), and platelet-derived growth factor (PDGF), were considered the key regulators of the wound healing process. [5][6][7] It has been established that impaired chronic wound healing is associated with decreased secretion of endogenous growth factors. Therefore, provision of exogenous growth factors at precisely timed intervals would provide stimulation to induce faster reepithelialization, as well as reduce the risk of infection.…”
Section: Introductionmentioning
confidence: 99%